Employment outcomes and policies in Sweden during recent decades - Anders Forslund (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2019)
The Swedish employment rate is high in an international comparison and has been rising during recent decades. This pattern is especially pronounced among the elderly and women and reflects labour supply behaviour in these groups. The policy survey in this report suggests that the main drivers of the high and rising Swedish employment rates can be found in policies for early retirement, old-age pensions and taxes and benefits.
Keywords: H30; H40; H53; H55; I28; J20; 330; Employment; Labour supply; Labour demand; Employment policies